The relationship between motivational factors and employee performance at Four Points by Sheraton Sandakan / Vanessa Lai - Lai, Vanessa (2016)
This study will explore about the relationship between motivational factors and employee performance at Four Points by Sheraton Sandakan. This research has involved 95 respondents which have been chosen randomly for this research. This research was conducted to identify which motivational factors that may influence the employee performance. The factors that have been chosen are payment, promotion and training. The data and information were collected using journal articles and questionnaire that has been distributed to employees at Four Points by Sheraton Sandakan. It has been analyzed by using the Statistical Package Social Science (SPSS). The findings show that the payment and promotion have relationship with employee performance. Therefore, some improvement should be taken by the organization in order to improve the motivational factors.